2020
DOI: 10.24018/ejbmr.2020.5.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Banks Credit, Macroeconomic Dynamics and the Performance of Small and Medium Scale Enterprises in Nigeria: A Non-Linear ARDL Approach

Abstract: This paper examines the impact of banks credit and macroeconomic dynamics on Small and Medium Scale Enterprises in Nigeria using annual data from 1992 – 2016. The long-run and short-run relationship amongst the variables were examined via the non-linear ARDL model. The Augmented Dickey Fuller (ADF) and Philip Perron’s (PP) test reveals that none of the variables were I(2). The Bounds test to cointegration confirms the existence of a long-run relationship. The non-linear ARDL results suggests that in both long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…This, therefore, indicate that Nigerian Banks turn over their assets into cash. Lastly, the loan-to-deposit ratio has a positive relationship with deposit money banks in Nigeria supporting the works of Kehinde&Solape (2021), Wuave, Henry & Paul (2020) and Ayunku (2017). However, the result is not significant, indicating a weak relationship.…”
Section: Discussion Of Resultssupporting
confidence: 65%
“…This, therefore, indicate that Nigerian Banks turn over their assets into cash. Lastly, the loan-to-deposit ratio has a positive relationship with deposit money banks in Nigeria supporting the works of Kehinde&Solape (2021), Wuave, Henry & Paul (2020) and Ayunku (2017). However, the result is not significant, indicating a weak relationship.…”
Section: Discussion Of Resultssupporting
confidence: 65%
“…The debate of whether bank liquidity affects bank financial performance is continuing as some previous research (Ayunku, 2017;Ifeacho & Ngalawa, 2014;Kosmidou et al, 2005, Quarshie & Djimatey, 2020 Theoretically, this is supported by a number of theories from earlier research. Yet, the empirical investigation into this relationship reveals a wide range of mixed results.…”
Section: The Relationship Between Liquidity and Banks' Financial Perf...mentioning
confidence: 91%
“…Furthermore, liquidity management ensures that there are sufficient cash balances for withdrawals and savings from customers, high assets quality and the ability to sustain all expenditures incurred (Olagunju, David & Samuel, 2011). The trigger of liquidity risk of banks, however, are misclassified of assets and liabilities in financial reporting and broaden loans and credit to high-risk borrowers (Ayunku, 2017). Studies have demonstrated that liquidity risk management plays a significant role in Islamic banking.…”
Section: Islamic Banks and Credit Riskmentioning
confidence: 99%